Inverse correlation between biofilm production efficiency and antimicrobial resistance in clinical isolates of Pseudomonas aeruginosa. (August 2021) - Yamani, Lamya; Alamri, Aisha; Alsultan, Afnan; Alfifi, Somaya; Ansari, Mohammad Azam; Alnimr, Amani
Abstract: This study assessed the correlation between biofilm formation in Pseudomonas aeruginosa strains with both the level of antibiotic resistance, and the number of virulence- and biofilm-related genes encoded. A total of sixty-six, non-replicate and prospectively collected P. aeruginosa strains were identified and tested. Potential ampD mutations that may impose resistance to extended-spectrum β-lactam (ESBL) agents were further explored. Of the sixty-six tested isolates, 40 demonstrated the multidrug resistance (MDR) phenotype, while twenty-six were non-MDR strains. An inverse correlation was observed between antibiotic resistance and the potential capacity to form biofilms. In addition, no correlation was observed between novel ampD mutations and the tendency for MDR isolates to acquire a β-lactam-resistant phenotype. The present study emphasizes the need for enhanced infection preventive measures in various hospital units, since both MDR and non-MDR P. aeruginosa isolates exhibited a high level of biofilm-forming capacity and the presence of virulence-associated genes.